Human metapneumovirus respiratory infection affects both innate and adaptive intestinal immunity - Sepúlveda-Alfaro, Javiera; Catalán, Eduardo A.; Vallejos, Omar P.; Ramos-Tapia, Ignacio; Madrid-Muñoz, Cristóbal; Mendoza-León, María J.; Suazo, Isidora D.; Rivera-Asin, Elizabeth; Silva, Pedro H.; Alvarez-Mardones, Oscar; Castillo-Godoy, Daniela P.; Riedel, Claudia A.; et al. (Frontiers in Immunology, 2024)
Respiratory infections are one of the leading causes of morbidity and mortality worldwide, mainly in children, immunocompromised people, and the elderly. Several respiratory viruses can induce intestinal inflammation and alterations in intestinal microbiota composition.Human metapneumovirus (HMPV) is one of the major respiratory viruses contributing to infant mortality in children under 5 years of age worldwide, and the effect of this infection at the gut level has not been studied. Here, we analyzed the distal effects of HMPV infection on intestinal microbiota and inflammation in a murine model, analyzing several postinfection times (days 1, 3, and 5). Six to eight-week-old C57BL/6 mice were infected intranasally with HMPV, and mice inoculated with a non-infectious supernatant (Mock) were used as a control group. We confirm that HMPV cannot infect the intestine, but we observed significant changes in the expression of IFN- in intestinal tissue, analyzed by qPCR, at days 1 and 3 post-infection as compared to the control group. Furthermore, we analyzed the frequencies of different innate and adaptive immune cells in the colonic lamina propria, using flow cytometry. The frequency of monocyte populations was altered in the colon of HMPV -infected mice at days 1 and 3, with no significant difference from control mice at day 5 postinfection. Moreover, colonic CD8 + T cells and memory precursor effector CD8 + T cells were significantly increased in HMPV-infected mice at day 5, suggesting that HMPV may also alter intestinal adaptive immunity. Additionally, we did not find alterations in antimicrobial peptide expression, the frequency of colonic IgA + plasma cells, and levels of fecal IgA. Some minor alterations in the fecal microbiota composition of HMPV -infected mice were detected using 16s rRNA sequencing. However, no significant differences were found in -diversity and relative abundance at the genus level. Therefore, these results indicate that HMPV can affect colonic immunity but does not significantly alter the microbiota composition, and further research is required to understand the mechanisms inducing these distal effects in the intestine.